Prevalencia, factores de riesgo y consecuencias asociadas a recesiones gingivales. Revisión de literatura. - Peña Villamizar, Cristian Eduardo (Universidad Antonio Nariño, 2021)
Gingival recession is defined as the apical migration of the gingival margin with respect to the enamel-cementum junction, which exposes the root cement, and results in a wider clinical crown in the occlusal-gingival direction, which leads to the appearance of aesthetic problems, dentinal hypersensitivity, root caries and abrasion. Its high prevalence around the world classifies it as a public health issue. Objective: To determine the prevalence, risk factors and consequences associated with gingival recessions through the systematic review of the scientific literature. Materials and Methods: A bibliographic review of the literature was carried out to identify the prevalence, risk factors and consequences of gingival recession around the world, indexed scientific articles hosted in search engines such and the base were selected. of data from the Antonio Nariño University in which a relationship with the gingival recession and the important issues mentioned in the main objective will be found. Results: A high prevalence of gingival recessions was reported in the articles included in this study, with a prevalence ranging from 54% to 95% both in first world countries and in developing countries. The factors mainly associated with gingival recession were traumatic brushing, orthodontia, gender, age, oral hygiene deficiency, occlusal trauma, oral piercing, smoking, and frenulum insertion. The main associated consequences were hypersensitivity, root caries, non-carious cervical lesions, plaque retention. Conclusion: There is a high prevalence of gingival recessions around the world. Gingival recession is a multifactorial disease that, if not treated, leads to aesthetic and functional alterations.